Analisis Dampak Sedimentasi Sungai Cibanjaran terhadap Penataan Ruang Permukiman di Desa Gunungsari Kecamatan Sukaratu Kabupaten Tasikmalaya - Desiani, Alya; Merdiani, Ghea Agistira; Fadjarajani, Siti; Nafisa, Igna Maulida; Darmawan, Cahya (UNM Geographic Journal, 2025)
Analysis of the impact of Cibanjaran river sedimentation on spatial planning. The main problem is what is the impact resulting from the sedimentation process in Cibanjaran River. The purpose of this research is to analyze the impact caused by sedimentation in Cibanjaran River and make strategies related to spatial planning around Cibanjaran River. The method used is descriptive qualitative with data collection techniques of observation, interview, and literature study. The results of the study state that the current condition of the land and body of Cibanjaran River is classified as a critical river category.  Mainly caused by the high intensity of sand mining activities in the foot area of Mount Galunggung, which is located adjacent to the upstream of the river. Mining activities are carried out without an adequate environmental management system, causing erosion and transportation of sediment material to the river body. Problems arose because most of the settlements grew spontaneously, not in accordance with the spatial plan, especially in river borders and disaster-prone zones. Many houses are built close to the river without regard to the boundaries. In conclusion, an adaptive and sustainable spatial planning strategy is needed. Important steps include enforcing riparian regulations, controlling development permits, relocating settlements in vulnerable zones, and integrating green open spaces as ecological buffers. Due to land degradation, infrastructure.